Development of a cross docking system model for distribution centers - Sheikholeslam, Mohammadnassir (2014)
Distribution is one of the important factors is in the warehousing and logistic industry which can play a major role in determining the total cost or the profit of the companies. This study presented a problem in the distribution systems and the delivery of the required products to the companies which receive their items through the distribution systems. The inventory level in the distribution centers has been one of the problems that the scholars have tried to solve by applying different methods. This study is trying to solve the problem of extra inventory and holding costs by developing a cross docking model for the distribution centers. The cross docking model has been developed by considering some of the required changes in the distribution center for storage elimination, such as scheduling the inbound and outbound containers and their sequence of entering and exiting the center and it has been developed in such a way that the products enter the distribution center and exit from it without any long term storage. Thus, the storing of the products in the distribution centers are eliminated and they are transformed into a cross docking center. The traditional distribution centers can profit from the advantages of cross docking distribution by trying to become a cross docking center and operate as one. The objective of the study is to develop a model based on the cross docking systems to assist the traditional distribution centers operate as a cross docking center and at the same time, delivering the required items of the customers. In order to achieve this objective, linear programming has been applied to develop a model to solve the problem as well as helping the distribution center of the company to turn into a cross docking center and operate as one. In the model, the concept of an auction has been considered, in which the profit of the distribution center needs to be maximized in the auction transaction. Therefore, the developed model is a maximization model to maximize this profit by considering the time, cost and profit parameters in the distribution center. The objective function of this maximization problem calculates the net income of the distribution center after the transaction is completed by considering the income of the distribution center from selling the products to the buyers, the costs that the center has to tolerate for buying the products from the sellers and the fixed costs and the cost of time. After the model was developed, it was programmed in Lingo software to achieve the optimum results in a short time and then it was implemented for a real life case to validate the model. Model implementation resulted in delivering the required items of the customers and helped the distribution center to be able to operate as a cross docking center and the inventory level was significantly reduced; before implementing the model, the inventory level of the company was about 900,000,000 R (Iranian Rials) and after it was implemented, the inventory level was reduced to about 200,000,000 R (Iranian Rials), which indicates 78% decrease in the level of inventory. Finally, by cross checking the achieved outcomes with the previous records of the company, the results indicated 8% increase in the profit of the company.